PENGARUH PENGELOLAAN MODAL KERJA DAN KEBIJAKAN HUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Ilham; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of working capital management dan debt policy on profitability at chemical sub-sector company listed in Indonesia Stocck Exchange (IDX). Working capital management ratios were used as independent variables is working capital turnonver, and ratio of debt policy is Debt to Asset Ratio (DAR). While being used as dependent variable is profitability Return on Asset (ROA). The populations of thisstudy are chemical sub-sector company listed in Indonesia Stock Exchange (IDX) for 2016-2020. The sampling technique in this study used Purposive Sampling and obtained a sample of 7 companies. Data used in this study is a secondary data financial reports. Analysis data using financial ratio analysis and multiple linear regressions analysis with SPSS 24.The results of the analysis shows that working capital management is still not effective, debt policy still has a ratio that is above the standard which indicates it is not healthy, profitability does not yet meet industry standards, the variable working capital management partially has significant effect on profitability, debt policy partially (t test) has negative effect on profitability, and simultaneous (f test) shows significant effect between working capital management and debt policy on profitability. The adjusted R square value is 0,424. This means that 42,4% of the variations of the two independent variables. While the remaining is influenced by variables that are not studied. Keywords: Working Capital Management, Debt Policy, Profitability